(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Since the beginning of human history, motherhood has been regarded as the most sacred and permanent attribute in many cultures. Although the roles and responsibilities of women have changed over time, due to social, political and economic events, the main responsibility of women has always been perceived as "motherhood". With the modern era, women have participated in social spheres therefore, certain expectations and expectations about motherhood were formed in terms of one-sided views. Although motherhood has evolved over the centuries, the expectations of mothers reflect similar characteristics in almost all cultures. They evoke patience, selflessness, compassion, charity, and unconditional love for children. There are various studies based on the concept of "motherhood" in psychology, anthropology and literature. However, for this study, in order to exemplify the mother concept, "motherhood" described by Adrienne Rich in "The Born Woman" (1976), as well as some mother images from the fiction texts of world literature were selected and comparatively analyzed. The purpose of this study is not to generalize the concept of "motherhood" for every culture in world literature, but based on the results of the analysis, it was to observe that the concept of "motherhood" is reflected in a similar way in many literary works belonging to different cultures. Therefore, this study will serve as a model for further comparative literature studies on motherhood and motherhood in world literature.